Universal service regulation and network effects in services of general economic interest in the European Union - Carlos Pateiro-Rodríguez; Federico Martín-Bermúdez; Carlos Pateiro-López; Manuel Escourido-Calvo (Economies, 2024)
The process of the liberalisation of services of general economic interest (SGEI) in the EU adopted the universal service (US) regulatory model. The objectives of the process were to strengthen free competition and improve social welfare. SGEIs have the characteristic of networked services and, as such, generate network externalities, as considered by the theory of market failures. This paper analyses the potential of the US in its role as a remedy for network externalities. In the SGEI context, the large number of participants reinforces network externalities, while limiting coordination mechanisms between users. Based on the relevant literature, a theoretical debate arises around the contribution of universal service obligations (USOs) to social welfare. A microeconomic analysis shows that USOs modify consumers' utility functions by shifting from inefficient market equilibria to efficient equilibria, thereby improving social welfare.
Keywords: 330; services of general economic interest; universal service; network externalities; social welfare